Coral reef resilience persisted for a millennium but has declined rapidly in recent decades - Zhang, Ting; Chen, Tianran; Liu, Sheng; Lin, Xianzhi; Li, Shu; Yan, Wen (Frontiers in Marine Science, 2023)
The lack of long-term records of coral community composition restricts our understanding of the contemporary ecological states of tropical reefs. Here we integrated paleo-ecological reconstruction, historical mortality evidence, and ecological survey data to determine the temporal variability in reef resilience of the Nansha atolls in the tropical western Pacific. Subfossil coral assemblages extracted from the reef cores exhibited no evidence of community shifts attributable to centennial-scale changes in El Niño variability during the last millennium, suggesting long-term stability in community structure and persistence of reef resilience. By contrast, ecological surveys revealed a major collapse in the reef ecosystem, and high-precision U-series dating of dead Acropora fragments indicated that this collapse occurred in recent decades and was especially relevant to several strong/extreme El Niño episodes. Frequent and intensive El Niño−Southern Oscillation and marine heatwaves have overwhelmed the reefs’ resistive and recovery capacity, thereby impairing reef resilience.